The Attitude of Higher Secondary School Teachers towards E-Learning in Purulia District of West Bengal, India - Karmakar, Banasree; Behera, Santosh Kumar (ATIKAN, 2015)
ABSTRACT: Educational technology has a tremendous capacity to provide best possible output in the process of education for both teachers and the students. Proactive use of technology is not the total answer to inequities and inadequacies that exist in educational programmes and teacher training, but it can provide at least a partial solution by strengthening a school ability to receive, transmit, and exchange information. E-learning is most expedient way in learning and training without having to go to school and training centers. E-learning is very much helpful for the teachers to their professional development. Keeping the importance of e-learning, an attempt has made through this study by the researchers to know the attitude of Higher Secondary School teachers towards e-learning in Purulia District of West Bengal, India. The present study was based on survey method, particularly the normative survey research method. One hundred fifty teachers (both male and female) teaching in Arts and Scienceâs streams were taken as representative sample of the whole population. An attitude scale was used for collecting the data. The means of both groups were tested for significance of difference by using âCRâ test. It was found that the attitude of Higher Secondary School teachers of Purulia District of West Bengal, India is neither more favourable nor unfavourable towards e-learning, i.e. satisfactory or average in attitude towards e-learning.KEY WORD: Attitude, school teacher and student, professional development, school ability, electronic learning, and transmit and exchange information.RINGKASAN: âSikap Guru-guru Sekolah Menengah Atas terhadap E-Learning di Distrik Purulia, Bengal Barat, Indiaâ. Pendidikan teknologi memiliki kapasitas yang luar biasa untuk memberikan hasil terbaik dalam proses pendidikan bagi para guru dan siswa. Penggunaan proaktif teknologi bukanlah jawaban total terhadap ketimpangan dan kekurangan yang ada dalam program pendidikan dan pelatihan guru, tetapi dapat memberikan setidaknya solusi parsial dengan memperkuat kemampuan sekolah untuk menerima, mengirimkan, dan pertukaran informasi. E-learning adalah cara yang paling bijak dalam pembelajaran dan pelatihan tanpa harus pergi ke sekolah dan pusat pelatihan. E-learning sangat banyak membantu guru dalam pengembangan profesi mereka. Menjaga pentingnya e-learning, sebuah upaya telah dilakukan melalui studi ini oleh peneliti untuk mengetahui sikap guru Sekolah Menengah Atas terhadap e-learning di Distrik Purulia, Bengal Barat, India. Penelitian ini didasarkan pada metode survei, khususnya metode penelitian survei normatif. Seratus lima puluh guru (baik laki-laki maupun perempuan) yang mengajar di bidang Seni dan Sains diambil sebagai sampel yang representatif dari seluruh populasi. Skala sikap digunakan untuk mengumpulkan data. Min kedua kelompok diuji untuk signifikansi perbedaan dengan menggunakan tes âCRâ. Ditemukan bahwa sikap guru Sekolah Menengah Atas di Distrik Purulia, Bengal Barat, India tidak lebih menyenangkan atau tidak menyenangkan terhadap e-learning, yaitu memuaskan atau rata-rata dalam sikap terhadap e-learning.KATA KUNCI: Sikap, guru dan siswa sekolah, pengembangan profesi, kemampuan sekolah, pembelajaran elektronik, serta pengiriman dan pertukaran informasi.Â Â About the Authors: Banasree Karmakar and Assist Prof. Dr. Santosh Kumar Behera are Research Scholar and Lecturer at the Department of Education, Sidho-Kanho-Birsha University, Purulia, West Bengal, India, Pin-723104. For academic purposes, the authors can be contacted via e-mails at: bkpurulia1991@gmail.com and santoshbehera.jkc@gmail.comHow to cite this article? Karmakar, Banasree & Santosh Kumar Behera. (2015). âThe Attitude of Higher Secondary School Teachers towards E-Learning in Purulia District of West Bengal, Indiaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(1) June, pp.1-10. Bandung, Indonesia: Minda Masagi Press and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (January 5, 2015); Revised (March 2, 2015); and Published (June 30, 2015).